ISOLATION OF LUPEOL, HPLC QUANTIFICATION AND ITS ANTI-HIV POTENTIALS - EKTA MENGHANI; SHARMA, SITA KUMARI (International Journal of Pharma and Bio Sciences, 2013)
Throughout human history natural products have been used as remedies to cure or treat various diseases. Even traditionally it has been surpassed by the amazing technology and pharmaceutical development that emerged with the promise of early healing. Humans continue to be affected by various diseases, mainly due to natural forces such as drug resistant microbes and insects. Consequently, an imperative need exists to connect the ethno pharmacological information with the newest drug discovery new active natural metabolites. Hence, it an urgent need to screen and isolate new natural products from plant sources and search for novel leads as therapeutic targets for future. Further, novel isolates and active fractions will also be part of active diet to enhance the health and lifestyle. Therefore, in present work attempts were made to search for new isolates with potential efficaciesviz. antioxidant, chemo preventive , cardio preventive, cardio protective and dietary supplement, among these our research attempts were made to isolation of lupeol from D. rubrum and its quantification. Lupeol exhibits a broad spectrum of biological activities and can be used as chemo preventive to avoid several diseases. Screening of lupeol suggested that it has positive potentials as anti HIV drug.